Atmospheric circulation patterns associated with avalanche cycles in the Troms region - Jenssen, Marius (UiT Norges arktiske universitet, 2018)
Snow avalanches endangers human lives and infrastructure situated in alpine environments during the winter season. Occurrence of avalanche activity is a product of processes taking place in the snow cover situated in steep terrain, which are governed by meteorological conditions induced by synoptic weather patterns. Avalanche forecasting can therefore better forecast avalanche activity if they understand the causal relationship between atmospheric circulation patterns and the boundary layer conditions responsible for the triggering of avalanches. Such an analysis has never previously been done for the studied region. This study assesses the occurrence of periods with high avalanche activity in Troms, Northern Norway with respect to the governing atmospheric circulation patterns and the meteorological conditions they induce. An avalanche activity dataset for the 16/17 winter season was used to distinguish nine avalanche cycles and meteorological observations for these cycles from local weather stations were used to describe the conditions leading to avalanche activity. Then, 500mb geopotential height maps, 850mb geopotential height maps and mean sea level pressure plots over the North Atlantic region were downloaded from NCEP/NCAR reanalysis project for avalanche cycle periods, and were used to categorize five synoptic situations responsible for these avalanche cycles. Avalanche cycle days are characterized by higher wind speeds and lower temperatures relative to the rest of the winter, causing wind transport of snow and delayed stabilization of the snowpack. The different synoptic types induces a range of meteorological settings causing avalanches, and the most prominent for avalanching are the induction of snow precipitation and wind, causing storm and wind slab avalanches during winter, and conditions favorable for warming events and subsequent wet snow avalanche activity in the end of the snow season.